2006
DOI: 10.1002/cpp.492
|View full text |Cite
|
Sign up to set email alerts
|

Distress and post‐traumatic stress disorders in high risk professionals: adult attachment style and the dimensions of anxiety and avoidance

Abstract: This study examines the relationship between adult attachment and psychological distress in a population of 544 people working for a security company and for the Belgian Red Cross. The results indicate that fearful-avoidant and preoccupied attached individuals report more stress than secure attached and insecure attached individuals of the dismissive type. Next, the same attachment styles appear to differentiate between individuals who do and individuals who do not develop a post-traumatic stress syndrome (PTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
5
24
0
2
Order By: Relevance
“…This finding suggests that associations between stressful life events and insecure attachment that have previously been identified (Waters et al, 2000) may generalize to samples of people with a diagnosis of psychosis and substance misuse. We found predicted associations between anxious attachment and PTSD that support findings in nonclinical samples (Declercq and Willemsen, 2006). This is cross-sectional study, and therefore, we cannot state with confident the direction of influence nor rule out associations being due to a third unmeasured variable.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding suggests that associations between stressful life events and insecure attachment that have previously been identified (Waters et al, 2000) may generalize to samples of people with a diagnosis of psychosis and substance misuse. We found predicted associations between anxious attachment and PTSD that support findings in nonclinical samples (Declercq and Willemsen, 2006). This is cross-sectional study, and therefore, we cannot state with confident the direction of influence nor rule out associations being due to a third unmeasured variable.…”
Section: Discussionsupporting
confidence: 82%
“…Avoidant attachment has been associated with a tendency to underreport distress (Dozier and Lee, 1995), thus obscuring any possible positive associations between interpersonal trauma, PTSD, and avoidant attachment. Previous research with nonclinical samples has similarly failed to find evidence of associations between attachment avoidance and PTSD (Declercq and Willemsen, 2006). The defensive style associated with avoidant attachment may provide a short-term coping mechanism for coping with feelings of distress.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Zakin, Solomon, and Neria (2003) found that the attachment style had a direct main effect and was inversely related to PTSD and psychiatric symptomatology in a group of war veterans. Declercq and Willemsen (2006) found that fearful-avoidant and anxious-preoccupied attached individuals reported more stress than did securely attached and insecurely attached individuals of the dismissive type. The adult attachment styles appeared to differentiate between individuals who do or do not develop posttraumatic stress syndrome after being confronted with a critical incident.…”
Section: Critical Incidents Attachment Style and Ptsdmentioning
confidence: 96%
“…There is some evidence to support this hypothesis, showing that emotion regulation strategies mediate the association between secure attachment and lower levels of PTSD symptoms [38]. Research has consistently shown that secure attachment is negatively associated with the subsequent development of posttraumatic stress disorder (PTSD) in a variety of adult trauma victims [39].…”
Section: Predictors Of Ptsdmentioning
confidence: 99%